Potenciali opisne analize omrežij za trženjsko načrtovanje na internetu - Kropivnik, Samo (Teorija in praksa, 2011)
As an up-to-date communication channel, the Internet can offer a lot to marketing communications although its specifics should be respected to effectively utilise it and to avoid counter-productive outcomes. In our study traditional approaches to Internet metrics are upgraded with insights offered by utilising exploratory network analysis methods to investigate how people actually browse through the Internet. The aim is to improve understanding of the conventional reach figures by gaining more knowledge about the relations between website audiences. The exploratory network analysis of automatic audience measurement logs yields valuable results: the visualisation of network browsing patterns, clusters of structurally equivalent sites and the projection of browsing probabilities on the clusters fully reveal the relations between audiences in Slovenia in 2006 and enable more sophisticated Internet marketing communications planning.
Keywords: Analiza omrežij; Network analysis; Blockmodeling; Bločno modeliranje; Internet; Marketing communication; Tržno komuniciranje; komunikacijski kanali; internet (računalniško omrežje)